Analysis of Organic Mulching on Soil Fertility and the Productivity of Sweet Corn (Zea mays saccharata Sturt L.) - Siti Mardiana; Sayyid Al-Fadhil Hasibuan; Sumihar Hutapea; Saipul Sihotang (Postgraduate, University of Mataram, 2023)
One of the causes of the low productivity of sweet corn is decreased soil productivity due to the leaching of nutrients by rainwater, tillage, and continuous application of inorganic fertilizers. The function of mulching is to increase soil moisture, suppress weed growth, and prevent soil erosion to create optimal soil conditions for plant growth. This study aimed to determine the effect of organic mulching on soil fertility and the productivity of sweet corn (Zea mays saccharata Sturt). This study used a Split Plot Design consisting of two factors, Tillage (P) and Organic Mulch (M) which had 6 levels, M0 = No Mulch, M1 = Plastic Mulch, M2 = Rice Straw Mulch, M3 =Cocopeat Mulch, M4 = Sawdust Mulch, M5 = Rice Husk Mulch. The results show that the M2 treatment of Rice Straw Mulch tended to increase soil fertility and had a significant effect on the productivity of sweet corn.